Impact of Professional and Scientific Societies’ Student Chapters on the Development of Underrepresented Undergraduate Students - Barnes, Lily; Grajales, Joshua; Velasquez Baez, Jocelyn; Hidalgo, Daniel; Padilla-Benavides, Teresita (Frontiers in Education, 2021)
Undergraduate students from historically underrepresented groups (URG) in institutions of higher education with a focus on science, technology, engineering, and math (STEM) careers often lack the support, resources, and community necessary to succeed in their desired fields. Through mentoring, webinars, seminars, and various research presentation opportunities, national societies and “locally-based” institutional student chapters provide atmospheres in which URG undergraduates can develop the skills required for academic and professional careers in STEM. In addition, national societies and student chapters contribute to outreach activities aimed towards the public in order to foster interest in STEM, as well as to primary and secondary school students to help them develop competency in skills and areas that lead to successful STEM careers. While many of these societies have operated for decades, the onset of the COVID-19 pandemic proved to be an unexpected roadblock, creating difficulties in terms of maintaining community dynamics and overcoming limits on in-person meetings. Though the conditions were challenging, they allowed for new perspectives on problem-solving in the face of adversity. The pandemic promoted the development of creative ways by which institutions and national societies could continue to educate students virtually. In this review, we discuss the role of national societies and student chapters in providing URG students with resources and skills to succeed in STEM fields while incorporating them into a community of like-minded peers with similar experiences.